Sex dependence of postoperative pulmonary complications - A post hoc unmatched and matched analysis of LAS VEGAS - Vermeulen, Tom D; Hol, Liselotte; Swart, Pien; Hiesmayr, Michael; Mills, Gary H; Putensen, Christian; Schmid, Werner; Serpa Neto, Ary; Severgnini, Paolo; Vidal Melo, Marcos F; Wrigge, Hermann; Hollmann, Markus W; et al. (Journal of clinical anesthesia, 2024)
STUDY OBJECTIVE: Male sex has inconsistently been associated with the development of postoperative pulmonary complications (PPCs). These studies were different in size, design, population and preoperative risk. We reanalysed the database of 'Local ASsessment of Ventilatory management during General Anaesthesia for Surgery study' (LAS VEGAS) to evaluate differences between females and males with respect to PPCs. DESIGN, SETTING AND PATIENTS: Post hoc unmatched and matched analysis of LAS VEGAS, an international observational study in patients undergoing intraoperative ventilation under general anaesthesia for surgery in 146 hospitals across 29 countries. The primary endpoint was a composite of PPCs in the first 5 postoperative days. Individual PPCs, hospital length of stay and mortality were secondary endpoints. Propensity score matching was used to create a similar cohort regarding type of surgery and epidemiological factors with a known association with development of PPCs. MAIN RESULTS: The unmatched cohort consisted of 9697 patients; 5342 (55.1%) females and 4355 (44.9%) males. The matched cohort consisted of 6154 patients; 3077 (50.0%) females and 3077 (50.0%) males. The incidence in PPCs was neither significant between females and males in the unmatched cohort (10.0 vs 10.7%; odds ratio (OR) 0.93 [0.81-1.06]; P = 0.255), nor in the matched cohort (10.5 vs 10.0%; OR 1.05 [0.89-1.25]; P = 0.556). New invasive ventilation occurred less often in females in the unmatched cohort. Hospital length of stay and mortality were similar between females and males in both cohorts. CONCLUSIONS: In this conveniently-sized worldwide cohort of patients receiving intraoperative ventilation under general anaesthesia for surgery, the PPC incidence was not significantly different between sexes. REGISTRATION: LAS VEGAS was registered at clinicaltrial.gov (study identifier NCT01601223).
Keywords: umělé dýchání; Sex Factors; Humans; Anesthesia, General; lidé středního věku; Risk Factors; Operating room; kohortové studie; celková anestezie; Female; rizikové faktory; Aged; dospělí; tendenční skóre; senioři; lidé; plicní nemoci; sexuální faktory; Cohort Studies; Postoperative Complications; Adult; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Lung Diseases; incidence; Incidence; General anaesthesia; Respiration, Artificial; mužské pohlaví; Postoperative pulmonary complications; Length of Stay; Outcome; délka pobytu; Intraoperative ventilation; Sex; Propensity Score